THE IMPACT OF MALNUTRITION ON GROSS MOTORIC GROWTH OF THE CHILDREN WHOSE AGE BETWEEN 3 MONTHS AND 2 YEARS OLD - Nike Aprilidia; Dominicus Husada; Juniastuti Juniastuti (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground: Malnutrition was one of the health problems that ware a challenge for developing countries. This problem had an impact on all aspects including economic, social, and health status of the nation. From these impacts, other health problems can occur, namely child development disorders, including impaired gross motor development and fine motor. The purposeof this research is to determine the malnutrition against motor development Method: This study was a case control study. The amount of the sample was 106 children, their age were around 3 months till 2 years old in Pakis Surabaya Health Centre. Simple random sampling was the technic which researcher used to take the case sample and purposive sampling was for the control ones. The independent variable was children’s malnutrition and the dependent variable were gross and fine motoric growth of the children. Data collecting was done by observing the children with KPSP questioner. Researcher used Chi-square to analyze the data. Result: Malnutrition didn’t affect children’s gross motoric growth (p= 0.34) and fine motoric growth (0.26). Conclusion: In Pakis primary health center there were 33% children with malnutrition, 28.3% children with gross motoric growth disorder and 35.8% children with fine motoric growth disorder. There wasn’t any association between children’s malnutrition with gross and fine motoric growth of the children.